TEACHERS' MOTIVATIONAL STRATEGIES IN TEACHING READING AT THE TENTH GRADE OF SMA NEGERI 1 PERCUT SEI TUAN - Putri Rohni Rejeki Sitio (Didaktika : Jurnal Pengabdian Masyarakat, 2026)
This study aimed to analyze the motivational strategies used by the teacher in teaching reading at SMA Negeri 1 Percut Sei Tuan. This study applied a qualitative descriptive research design. The data were collected through classroom observation using observation sheets and classroom recordings during the teaching and learning process. The data were analyzed based on the motivational teaching practice framework proposed by Dörnyei (2001), namely creating basic motivational conditions, generating initial motivation, maintaining and protecting motivation, and encouraging positive self-evaluation. The findings showed that the teacher implemented all four categories of motivational strategies during reading instruction. Among the four categories, maintaining and protecting motivation became the most dominant strategy, as it was frequently applied through group discussions, teacher encouragement, vocabulary assistance, and interactive classroom activities. The teacher also implemented creating basic motivational conditions by establishing a supportive classroom atmosphere, generating initial motivation by relating reading materials to students’ daily experiences, and encouraging positive self-evaluation through positive feedback and reflection activities. The implementation of these motivational strategies helped increase students’ participation, engagement, and confidence during reading activities and supported a more interactive learning environment.